Agriculture, water use in southern Africa: applying the concept of integrated water resources management - McCartney, Matthew P.; Sally, Hilmy; Senzanje, Aidan (2004)
More than 80% of annual water withdrawal in southern Africa is for agricultural purposes. Much of the region experiences semi-arid to arid climates and water resources vary considerably. In many countries water managcmcnt is complicated by the frequent recurrence of droughts. Improved management of water resources is a pre-requisite to future development in the region. This paper presents the concept of Integrated Water Resources Management (IWRM) which has been widely proffered as a modern approach to water management that will ensure long-term benefits whilst simultaneously protecting the environment and ensuring sustainability. The implications of IWRM for agriculture in southern Africa are assessed. Benefits for the agricultural sector include reduced vulnerability to climatic variability, improved productivity and a more rational and transparent approach to decision-making. However, there remain many constraints to the application of IWRM including lack of quantitativc information pertaining to water use and a wide range of institutional and other socioeconomic harriers. An evaluation of changes required to introduce IWRM within the agricullural sector, under arid and semi-arid conditions, is presented.